Pastoral paradises and social realism: cinematic representations of suburban (2013)
Th e cinema in its literal sense has been both a landmark of the suburban-built environment and staple source of popular culture in the post-war era: with the Regals, Gaumonts, UCGs and ABCs off ering relatively cheap escapism from everyday mundanity and routine. Th e cinema has served the function of a venue for suburban courtship for couples and entertainment for fully formed family units with the power to move audiences to the edge of their seats in suspense or to tears – be that laughter or of sadness. While the VHS and advent of domestic video recorders was seen to threaten the very existence of the cinema, many suburban areas have seen the old high street picture palaces replaced/displaced/ succeeded by out-of-town complexes where suburbia has sometimes been the subject on the screen as well as the setting of the multiplex they are screened in. In the United States the suburb has variously equated with idyllic family dreamhouse, horror-laden land of dark undercurrent and stomping ground for adolescent angst in fi lms from which changes can be tracked from the innocence of the suburbia of the all-American goodlife in the 1950s to its more recent portrayal as shopping mall-dominated territory from the 1980s onwards overrun by slackers by the 1990s. British cinema has tended to pride itself by being in a more ‘slice of life’ social realism vein. Th is chapter turns to the silver screen (or DVD release) to discuss full-length feature fi lms featuring suburbia. Th e consideration of suburbia onscreen will continue in Chapter 5 addressing televisual (small-screen) representations.